Asymmetric dihydroxylation route to (R)-(-)-octopamine, (R)-(-)-tembamide and (R)-(-)-aegeline - Sadyandy, R.; Fernandes, R. A.; Kumar, P. (Arkivoc, 2005)
A simple and efficient asymmetric synthesis of (R)-(-)-octopamine 1, (R)-(-)-tembamide 2 and (R)-(-)-aegeline 3 is described for the first time employing the Sharpless asymmetric dihydroxylation (AD) as the source of chirality. (C) 2004 Elsevier Science Ltd. All rights reserved.
Keywords: aegeline; Asymmetric synthesis; Dihydroxylation; octopamine; tembamide

Co-catalyzed reductive cyclization of azido and cyano substituted alpha,beta-unsaturated esters with NaBH4: enantioselective synthesis of (R)-baclofen and (R)-rolipram - Paraskar, A. S.; Sudalai, A. (Tetrahedron, 2006)
Sodium borohydride in combination with a catalytic amount of CoCl, has been found to be an excellent catalytic system in reductive cyclizations of suitably substituted azido and cyano groups of alpha,beta-unsaturated esters to afford gamma and delta-lactams in high yields. The process has been demonstrated for the enantioselective synthesis of (R)-baclofen, (R)-rolipram, and (R)-4-fluorophenylpiperidinone, a key intermediate for (-)-paroxetine. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Asymmetric synthesis; cobalt chloride; gamma and delta-lactams; reduction; sodium borohydride

Enantioselective synthesis of (-)-cytoxazone and (+)-epi-cytoxazone, novel cytokine modulators via sharpless asymmetric epoxidation and L-proline catalyzed mannich reaction - Paraskar, Abhimanyu S.; Sudalai, Arumugam (Tetrahedron, 2006)
A short and efficient enantioselective synthesis of (-)-cytoxazone and its stereoisomer (+)-epi-cytoxazone, novel cytokine modulators, has been described with good yield and enantioselectivity. Ti-catalyzed Sharpless asymmetric epoxidation of allyl alcohol and L-proline catalyzed three-component Mannich reaction constitute the key steps in introducing stereogenicity into the molecule. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: aminohydroxylation; Asymmetric synthesis; epoxidation; Mannich reaction; Oxidation; Ozonolysis

Short enantioselective synthesis of (-)-chloramphenicol and (+)-thiamphenicol using tethered aminohydroxylation - George, Shyla; Narina, Srinivasarao V.; Sudalai, Arumugarn (Tetrahedron, 2006)
An efficient enantioselective synthesis of (-)-chloramphenicol (1) and (+)-thiamphenicol (2) is described. These antibiotics have been synthesized from commercially available 4-nitrobenzaldehyde and 4-(methylthio)benzaldehyde, respectively, using tethered amino-hydroxylation and Sharpless asymmetric epoxidation as the chirality inducing steps. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: asymmetric epoxidation; Asymmetric synthesis; Kinetic resolution; Tethered aminohydroxylation

First asymmetric total synthesis of penarolide sulfate A(1) - Mohapatra, Debendra K.; Bhattasali, Debabrata; Gujar, Mukund K.; Khan, Mohammad Islam; Shashidhara, K. S. (European Journal of Organic Chemistry, 2008)
Penarolide sulfate A(1), with three contiguous stereogenic centers on a macrocyclic skeleton, affords promise as an alpha-glucosidase inhibitor. Herein, we describe the first asymmetric total synthesis of this natural product. A stereoselective strategy for rapid assembly of the complete framework of the 30-membered macrocyclic core is delineated herein. Sequential amidation and intramolecular Sonogashira cross-coupling reactions were pivotal to the success of our efforts. ((C) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2008)
Keywords: Asymmetric synthesis; C-C coupling; Dihydroxylation; epoxidation; Macrocycles; Regioselectivity; Total synthesis

Enantio- and diastereocontrolled total synthesis of (+)-strictifolione - Kumar, Pradeep; Pandey, Menaka; Gupta, Priti; Naidu, S. Vasudeva; Dhavale, Dilip D. (European Journal of Organic Chemistry, 2010)
A concise and practical enantioselective synthesis of (+)-strictifolione has been achieved in high diastereomeric excess using Jacobsen's hydrolytic kinetic resolution, proline-catalyzed sequential alpha-aminoxylation and Horner-Wadsworth-Emmons olefination of aldehyde and cross olefin/ring-closing metathesis as the key steps.
Keywords: Asymmetric synthesis; Hydrolytic kinetic resolution; lactones; Natural products; organocatalysis; Ring-closing metathesis; Total synthesis

Bidentate ligand-catalyzed enantioselective addition of RZnX to benzaldehyde - Jagtap, Ravindra S.; Joshi, Navalkishore N. (Tetrahedron Letters, 2011)
{Enantioselective addition of RZnX (R = alkyl
Keywords: 1; 2-Addition; Asymmetric synthesis; Chelating ligands; Organozinc

Organocatalytic asymmetric 1,6-addition reactions - Biju, Akkattu T. (Chemcatchem, 2011)
Keywords: Asymmetric synthesis; catalysis; Michael addition; organocatalysis; phase-transfer catalysis

Protecting-group-free diastereoselective total synthesis of (+/-)-6-epi-cleistenolide and chemoenzymatic synthesis of (-)-6-epi-cleistenolide - Mahajan, Pankaj S.; Gonnade, Rajesh G.; Mhaske, Santosh B. (European Journal of Organic Chemistry, 2014)
A short, efficient, practical, and protecting-group-free diastereoselective total synthesis of (+/-)-6-epi-cleistenolide (1) has been achieved in five steps in 60% overall yield. The use of a chemoenzymatic approach also gave (-)-6-epi-cleistenolide (1) (>99.9% ee). The Achmatowicz reaction, chemoselective oxidation of a hemiacetal, diastereoselective 1,3-anti reduction of alpha-hydroxy ketone, and enzymatic resolution of a 1,3-diol are the key features of this linear total synthesis. The synthetic strategy demonstrated in this paper could be extended for an asymmetric total synthesis of (-)-cleistenolide (1) and related biologically active natural products.
Keywords: Asymmetric synthesis; diastereoselectivity; Enzyme catalysis; Lipases; Oxygen heterocycles; Total synthesis

Comprehensive study on the effect of acid additives in 1(R),2(R)-Bis[(S)-prolinamido]cyclohexane catalyzed direct asymmetric aldol reactions in aqueous media - Bhowmick, Sudipto; Kunte, Sunita S.; Bhowmick, Kartick C. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2015)
The catalytic efficacy of (1R,2R)-bis[(S)-prolinamido]cyclohexane 1, prepared from the readily available natural amino acid L-proline has been studied for the direct asymmetric aldol reaction of cyclohexanone with substituted benzaldehydes at room temperature in presence of various acid additives. A wide variety of acids e.g. aliphatic fatty acid, chiral acid, sulphonic acid, aromatic acid, etc. have been used as additive for the aldol reaction in aqueous media. A loading of 10 mol% of catalyst 1 is employed in this reaction, and good yields (up to 98% yield), diastereoselectivity (up to 96% de) and enantioselectivities (up to 87% ee) can be achieved in aqueous media within very short reaction time (1-4 hours).
Keywords: acid additives; aqueous media; Asymmetric synthesis; direct aldol reaction; organocatalysis

Concise enantioselective synthesis of naturally active (S)-3-hydroxypiperidine - Dey, Soumen; Karabal, Pratibha U.; Sudalai, Arumugam (Synthetic Communications, 2015)
A short and efficient enantioselective synthesis of natural product (S)-3-hydroxypiperidine has been achieved starting from commercially available raw materials employing two catalytic routes: (i) cocatalyzed hydrolytic kinetic resolution (HKR) of racemic methyl-3-(oxiran-2-yl)propanoate; (ii) proline-catalyzed -aminooxylation followed by Horner-Wardsworth-Emmons olefination in high enantiomeric purity (97% ee) and high overall yield (38%).
Keywords: Asymmetric synthesis; bioactivity; Enantioselectivity; Natural products; organocatalysis

Proline-catalyzed alpha-aminooxylation of beta-amino aldehydes: access to enantiomerically pure syn- and anti-3-amino-3-aryl-1,2-alkanediols - Venkataramasubramanian, V.; Kiran, I. N. Chaithanya; Sudalai, Arumugam (Synlett, 2015)
A new synthetic method for enantioselective synthesis of syn 3-amino-3-aryl-1,2-alkanediols via praline catalyzed alpha-aminaoxn y ylation of beta-amino aldehydes des are described. This methodology is successfully applied to a concise and protecting group-free asymmetric synthesis of (-)-cytoxazone (+)-epi-cytoxazone and formal synthesis of N-thiolated 2-oxazolidinone.
Keywords: amino aldehydes; Asymmetric synthesis; catalysis; diastereoselectivity; Enantioselectivity; Natural product

Enantioselective modular total synthesis of macrolides Sch725674 and C-4-epi-Sch725674 - Sharma, Brijesh M.; Gontala, Arjun; Kumar, Pradeep (European Journal of Organic Chemistry, 2016)
The convergent total synthesis of Sch725674 has been accomplished by starting from (R)-1,2-epoxyheptane and assembling five modules in a highly stereoselective manner to give the final product in 6.6% overall yield. The same strategy was extended to the synthesis of its C-4 epimer. Key reactions of the synthetic pathway include a Jacobsen hydrolytic kinetic resolution of an epoxide followed by its regioselective opening through a Yamaguchi-Hirao alkynylation, and ring-closing metathesis reaction to furnish the unique 14-membered ring macrolactone. In addition, the influence of protecting groups on the efficiency of the ring-closing metathesis (RCM) macrocyclization has been studied to maximize its yields.
Keywords: Asymmetric synthesis; Hydrolytic kinetic resolution; Macrocycles; Metathesis; Natural products

Concise formal synthesis of (-)-(6R,11R,14R)-colletallol via D-proline catalysed alpha-aminooxylation-Wittig olefination strategy - Dey, Soumen; Gadakh, Sunita; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2019)
An efficient enantioselective formal synthesis of marine macrolide (-)-(6R,11R,14R)-colletallol has been achieved starting from commercially available raw materials. The key reactions include the D-proline catalyzed a-aminooxylation of aldehyde followed by Horner-Wardsworth-Emmons olefination in a sequential fashion to give the macrolide key intermediate 5 in high enantiomeric purity (97% ee) and high overall yield (32%).
Keywords: alpha-aminoxylation; Asymmetric synthesis; Enantioselectivity; Natural products; organocatalysis

Vinylogous michael addition of 3-alkylidene-2-oxindoles to beta,gamma-unsaturated alpha-keto esters by bifunctional cinchona alkaloids - Jaiswal, Manish K.; Kumar, Rajesh; Singh, Sanjay; Jain, Shailija; Vanka, Kumar; Singh, Ravi P. (European Journal of Organic Chemistry, 2020)
A highly enantioselective vinylogous Michael addition of 3-alkylidene-2-oxindoles with beta,gamma-unsaturated alpha-keto esters using a bifunctional tertiary-amine thiourea catalyst is demontsrated. The challenging Michael reaction with the beta,gamma-unsaturated alpha-keto esters has been accomplished due to the synchronized H-bond guided dual activation of vinylogous nucleophile and electrophile by catalyst. The reaction afforded product in high yield while resulting in excellent stereocontrol (> 19:1E/Zand upto 99 %ee).
Keywords: 3-Alkylidene-2-oxindoles; Asymmetric synthesis; beta; gamma-Unsaturated alpha-keto esters; Michael adduct; Vinylogous Michael addition

Ni-catalyzed highly enantioselective synthesis of sulfur protected P-stereogenic supramolecular phosphine - Koshti(S), Vijay S.; Chandanshive, Amol C.; Mote, Nilesh R.; Chikkali, Samir H. (Journal of Chemical Sciences, 2021)
As phosphines readily invert, the synthesis of P-chiral phosphines is a challenging task and has been rarely investigated. We report the synthesis of a nickel complex [Ni-((S,S)Me-FerroLANE)(phenyl)(I)] (Ni-Cat.1) and its performance in a P-C coupling reaction to generate P-chiral phosphine. The Ni-Cat.1 was synthesized by mixing ligand (S,S) Me-FerroLANE with the metal precursor [(diphenylphosphanyl)nickel(phenyl)(I)] in good yield. Ni-Cat.1 was characterized using different spectroscopic and analytical techniques. Treatment of racemic methyl(phenyl)phosphine (1) with 1-(3-iodophenyl)urea (2) produced the corresponding P-chiral supramolecular phosphine (3). Optimization of reaction parameters produced sulfur protected phosphine N-(3-(methyl(phenyl)phosphorothioyl)phenyl)formamide (3') with excellent enantiomeric excess (99% ee) and moderate conversion (51%).
Keywords: Asymmetric synthesis; Nickel catalyst; P-C coupling; P-Stereogenic phosphine; supramolecular ligands

Asymmetric synthesis of inositol derivatives - Patil, Nivedita T.; Sarkar, Nitai; Mysore, S. Shashidhar; Gonnade, Rajesh G. (Tetrahedron, 2024)
Both the enantiomers of racemic 4- O -tosyl-6- O -benzyl- myo -inositol-1,3,5-orthoformate ( 2 ) were isolated by preferential crystallization and used to synthesize several enantiomeric myo -inositol derivatives - natural ononitol, natural laminitol, precursors for myo -inositol phosphates and an oxabicyclo [2.2.1] heptane derivative. This work demonstrates the potential of the enantiomeric tosylates D2 and L2 to serve as versatile starting materials for the absolute asymmetric synthesis of inositol derivatives and other natural products from symmetric myo -inositol since no optically active molecular entity was required for the resolution of 2.
Keywords: Asymmetric synthesis; Carbohydrate; Cyclitol; Inositol; Natural product